IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM AT THE DRIVING SCHOOL - Qolbiyah, Aini; Sonzarni, Sonzarni; Ismail, Muhammad Aulia (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to discuss the implementation the independent learning curriculum at the driving school. This research is a literature study, namely research that is sourced from library materials using a qualitative approach. In this case, the researcher explored a number of data, both primary data and secondary data with the following steps: reading and studying in depth primary data such as books, journals, articles, theses and dissertations related to the discussion of the independent learning curriculum at the driving school. The conclusion of this study is that The existence of facilities and infrastructure is also very supportive of the successful implementation of the implementation of the independent curriculum in driving schools. The assessment in the independent curriculum at the driving school that is applied is a comprehensive assessment that encourages students to have competencies according to their talents and interests without burdening students with the minimum score. The National Examination is abolished and replaced with a Minimum Competency Assessment and Character Survey, each school is given full authority regarding those related to national exam policies, Simplification of Learning Implementation Plans.